2023
DOI: 10.1136/bmjopen-2022-068481
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of patients with Long COVID: a qualitative study in the UK

Abstract: BackgroundLong COVID is a rapidly evolving global health crisis requiring interdisciplinary support strategies that incorporate the lived experience of patients. Currently, there is a paucity of research documenting the day-to-day experiences of patients living with Long COVID.ObjectiveTo explore the lived experience of Long COVID patients.Study designLongitudinal, observation study.SettingAn inductive, data-driven, qualitative approach was used to evaluate hand-written diaries obtained from individuals who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Some findings from this study show similarities with other Long Covid studies. Most notably, the varying range of symptoms experienced, [4][5][6][7][8] the lack of Long Covid awareness among some population groups, 7,43,44 self-doubt regarding Long Covid as a cause for symptoms, 7 symptoms as a barrier to accessing care, 43 problems accessing primary care, 6,10,45 experiences of symptoms being dismissed, 10,46,47 seeking support outside the NHS and making behavioural changes, 6,11,[45][46][47][48] as well as stigma 6,47,48 and discrimination 45 which can all act as barriers to obtaining support, care and treatment for symptoms. Parallels can also be drawn with Ireson et al 46 who suggest the experiences of people living with Long Covid, equate to epistemic injustice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some findings from this study show similarities with other Long Covid studies. Most notably, the varying range of symptoms experienced, [4][5][6][7][8] the lack of Long Covid awareness among some population groups, 7,43,44 self-doubt regarding Long Covid as a cause for symptoms, 7 symptoms as a barrier to accessing care, 43 problems accessing primary care, 6,10,45 experiences of symptoms being dismissed, 10,46,47 seeking support outside the NHS and making behavioural changes, 6,11,[45][46][47][48] as well as stigma 6,47,48 and discrimination 45 which can all act as barriers to obtaining support, care and treatment for symptoms. Parallels can also be drawn with Ireson et al 46 who suggest the experiences of people living with Long Covid, equate to epistemic injustice.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6][7][8] These symptoms can have wide ranging negative social impacts that include inhibiting ability to engage in employment and creating financial burdens. 4,[9][10][11] Health inequalities exist between different population groups in England. 12,13 Inequalities were evident prior to COVID-19 but the pandemic has exacerbated them and increased their visibility.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8] It can have wideranging negative social impacts that include inhibiting the ability to engage in employment and creating financial burdens. 4,[9][10][11] Health inequalities exist between different population groups in England. 12,13 Inequalities were evident before COVID-19 but the pandemic has exacerbated them and increased their visibility.…”
Section: Introductionmentioning
confidence: 99%
“…Long Covid can cause varying symptoms and impact on daily life, including, but not limited to, fatigue, breathlessness, headache, cognitive dysfunction, chest pain, muscle/joint pains, cough, disturbed sleep and neuropsychiatric symptoms 1,4–8 . It can have wide‐ranging negative social impacts that include inhibiting the ability to engage in employment and creating financial burdens 4,9–11 …”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research on the lived experience of PwLC [18 19] including their self-reported barriers to accessing healthcare [13 14]. Until recently, however [15], none have focussed on community rehabilitation.…”
Section: Introductionmentioning
confidence: 99%